Pengolahan Limbah Jelantah Menjadi Lilin Aromaterapi Sebagai Pendongkrak Potensi Ekonomi Dan Peningkatan Kesehatan Masyarakat - Agustina Dwi Prastanti; Bagus Abimanyu; Dwi Rochmayanti; Rini Indrati; Darmini Darmini (MATAPPA: Jurnal Pengabdian Kepada Masyarakat, 2022)
The purpose of this training is to provide education on the use of used cooking oil household waste into aromatherapy candles through intensive assistance to improve the economic level and public health. The community service method used is lecture, discussion and direct practice. The community service element involves the head of the PKK RT, RW and health cadres. The direct practice of processing household waste cooking oil by the community obtained results in the form of aromatherapy candles where the used cooking oil was cleared up first as the basic ingredient. Aromatherapy candles are ready to use after a period of 2 (two) days to get maximum wax density. The benchmark for the success of making aromatherapy candles from used cooking oil is assessed from candles that can be used as lighting when the lights go out as well as aromatherapy as well as room decoration, repellent for flies, mosquitoes and other insects.